Application of Simple Technology for Promoting Micro, Small, and Medium Enterprises: A Digital Signboard Implementation at Nenek Kasiani’s Shop - Hulu, Fitria Nova; Nasution, Tuti Adi Tama; Hutabarat, Nicodemus Firman River; Hasnita, Ulfa (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2025)
This community service activity was carried out as a form of support for Micro, Small, and Medium Enterprises (MSMEs), especially Warung Nenek Kasiani, in facing the challenges of business promotion in the digital era. One of the problems faced by traditional MSMEs is the minimal use of attractive and effective promotional media. Through this activity, the Independent Community Service (PMKM) team conducted outreach and provided assistance in installing a digital signage in the form of LED-based running text at the stall. This simple innovation aims to increase the visual appeal of the business, strengthen the stall's identity, and help attract a wider consumer interest. The results of this activity show an increase in public attention to the stall and an increased awareness of MSMEs in utilizing digital technology practically. This activity is expected to become a model of sustainable service and can be replicated by other MSMEs in various regions.Keywords: MSMEs, digital signage, running text, promotion, community service, traditional stalls